How school governance affects teachers’ organizational citizenship behavior? - Heru Suparman; Widodo Widodo (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Organizational citizenship behavior (OCB) is a critical determinant for teachers and school organizations. Hence, this study investigates school governance affects teachers’ OCB through organizational commitment. The study used a survey method which was carried out by distributing Likert scale questionnaires to 275 teachers in public junior high schools in Indonesia. Data analyses using structural equation modeling (SEM) supported by common method biases (CMB) followed descriptive and correlational statistics. The results show that school governance directly affects teachers' OCB, organizational commitment directly affects teachers' OCB, school governance directly affects organizational commitment, and school governance indirectly affects teachers’ OCB through organizational commitment. This finding promotes a new model of school governance affects teachers’ OCB through organizational commitment. Accordingly, this study suggests that school management improves OCB teachers through management engineering based on school governance and organizational commitment. Meanwhile, researchers can discuss the model before it is adapted or adopted in their future research projects.